THE INFLUENCE OF VILLAGE FINANCIAL SYSTEM APPLICATIONS (SISKEUDES), AND INTERNAL CONTROL SYSTEMS ON THE QUALITY OF FINANCIAL STATEMENTS WITH RESOURCES COMPETENCE HUMANS AS VARIABLES MODERATOR (Case Study of Village Government in Sukodadi District) Lamonga - Mahmudah, Annita; Dilasari, Aranta Prista; Susanti, Ayu Dwi (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
This study aims to determine the effect of the Village Financial System Application (Siskeudes), Internal Control System, on the Quality of Financial Reports moderated by Human Resource Competence. The object of this research is the villages in Sukodadi District, Lamongan Regency. The research sample was 10 villages with village heads, village secretaries, and village treasurers/village finance heads as respondents. This research uses quantitative methods with primary data collection, namely questionnaires. Sampling using purposive sampling. Based on the process of distributing questionnaires, a sample of 30 respondents was obtained. The data of this study were analyzed using Moderated Regression Analysis (MRA) using the SPSS Version 26 software application. The results showed that human resource competence did not moderate the effect of village financial system applications, or the influence of the internal control system on the quality of village government financial reports. While the application of the village financial system and the Internal Control System have a significant effect on the Quality of the Village Government Financial Reports.